Genetic Algorithms to Improve Mask and Illumination Geometries in Lithographic Imaging Systems - Fühner, Tim; Erdmann, Andreas; Farkas, Richard; Tollkühn, Bernd; Kókai, Gabriella (Applications of Evolutionary Computing - EvoWorkshops 2004: EvoBIO, EvoCOMNET, EvoHOT, EvoISAP, EvoMUSART, and EvoSTOC, 2004)
This paper proposes the use of a genetic algorithm to optimize mask and illumination geometries in optical projection lithography. A fitness function is introduced that evaluates the imaging quality of arbitrary line patterns in a specified focus range. As a second criterion the manufacturability and inspectability of the mask are taken into account. With this approach optimum imaging conditions can be identified without any additional a-priori knowledge of the lithographic process. Several examples demonstrate the successful application and further potentials of the proposed concept. © Springer-Verlag 2004.
UnivIS-Import:2015-04-16:Pub.2004.tech.IMMD.IMMD2.geneti_6